Enhancement of the Conventional Sri Lankan National Fuel Pass to a Comprehensive Fuel Station Application - G.P. Bamunusingha; I.I.E. Gunawardana; K.M.N. Jayamini; M.D.S.U Jayawardana; D.I. De Silva; S. Vidhanaarachchi (International Journal of Engineering and Management Research, 2022)
Due to the economic crisis in Sri Lanka. There was a fuel supply problem because of the lack of foreign currency. Even though the government tried to supply the fuel demand, it was unsuccessful due to refueling the fuel since all people were trying full tank their vehicles. Therefore, the government took a new approach by creating a simple QR code scanning application. Even though the application was developed, the features were minimal. To give good insight and emotions to the users, improve their user experience, and maximize user usability Fuel Station App was developed. This is capable of viewing, Downloading, Regenerating the QR, Managing and altering the user profiles, and calculating the fuel consumption of the user vehicle. After the development phase, the app was tested, and the results were collected from the study. The survey confirmed that the users prefer the proposed solution to pump fuel and get good insights from the application.